Prevalence of anti-herpes simplex virus type 1 among dental students of Birjand University of Medical Sciences, Iran, 2017-2018: Short Communication - Parvin Parvaie; Saideh Ebrahimian Baghan; Mahmood Zardast; Gholamreza Sharifzadeh; Freshteh Osmani (مجله دانشگاه علوم پزشکی بیرجند, 2021)
Herpes simplex virus is considered one of the most common human infections in most parts of the world, among which, herpes simplex virus 1 (HSV-1) is one of the most important human pathogenic viruses that cause numerous skin and oral lesions. Practitioners of the dental profession and related fields are in close contact with numerous patients referring to dental clinics and are at risk of cross-infection. Regarding this, one of the infections that dental professionals are exposed to is herpes simplex virus infection. This study aimed to evaluate the level of HSV1 antibody among dental students of Birjand in 2018-2019. This cross-sectional study was performed on 100 dental students of Birjand University of Medical Sciences, Iran. After obtaining informed consent, a peripheral blood sample (5 ml) was collected from participants and the presence of anti-virus antibody was examined using an Anti-Herpes-1 IgG kit with the enzyme-linked immunosorbent assay. It was revealed that 41% of the subjects had anti-herpes type 1 antibodies. Based on data analysis, the prevalence of HSV1 antibody was higher in pre-clinical and clinical level than in basic science; however, there was no significant relationship between studentschr('39') educational level and antibody prevalence.